Food consumption, lifestyle and its influence on the aging process (Research, Society and Development, 2019)
Objective: To show the influence of eating patterns and lifestyles on aging. Method: This study is an integrative review of the literature that relates food consumption and lifestyle in the aging process. It consisted of five steps: elaboration of the guiding question, search in the literature, critical analysis of data, integration of data and presentation of results. We used the databases SciElo, LILACS and Pubmed with the descriptors "Food consumption, lifestyle, aging". After the selection of the studies, 15 articles were used for structuring this integrative review. Results: Regarding food, the studies highlighted the importance of regulator food consumption and the reduction of foods with high caloric value. The practice of regular physical activity has shown to be a great ally in improving the quality of aging. As for smoking and alcoholism, practices that are incompatible with healthy aging are considered. Most of the selected studies worked with elderly people in the age group from 60 years and revealed that many of them do not have the habit of smoking and consuming alcoholic beverages. Conclusion: Adequate diet and physical activity are determinants that positively influence the active aging process, while smoking and alcoholism can lead to chronic morbidity. The studies also reveal the need to carry out more educational actions aimed at this population group in order to stimulate the improvement of health and quality of life.